An Innovation based Entrepreneurship - Amal Joseph (AG Volumes, 2021)
The purpose of this research is to examine and elucidate the functions that entrepreneurship’s innovation plays. Entrepreneurship and innovation both need creativity as a means of affecting culture as a whole, and innovation is no exception. Drucker. Risk-taking, innovative concept creation, and hard labour are necessary in the entrepreneurship industry to generate new innovation in company. The entrepreneur must be more aware of the fast changes that are taking place in many different areas at this time. As a part of this discussion, we’ll look at some of the most current models that connect entrepreneurship with innovation. Finally, a thorough framework for future concerns is presented in the last chapter.